Zur Geschichte deutscher Wissenschaftssprachen. Aufsätze, Essays, Vorträge und die Abhandlung „Erkenntnis und Sprache in Goethes Naturwissenschaft“ - Schiewe, Jürgen (De Gruyter, 2021)
The history of German scientific language from the 16th century to the present day is the primary research focus of the linguist and medievalist Uwe Pörksen. Twenty chapters covering forty years of her work nuance this theme, which extends beyond disciplinary boundaries. Published for the first time, Pörksen’s 1974 habilitation thesis Knowledge and Language in Goethe’s Writings on Natural Science is the center of her thought and research.